Adaptation to Accelerated Digitalization in the Context of a Pandemic: Comparative Study of Higher Education Systems in Russia and Belarus - L. G. Titarenko (Moscow Polytechnic University, 2022)
The article reflects the input of the first and second waves of the pandemic on the higher education system in Russia and Belarus. The purpose of the article is to identify the level of adaptation to the widespread use of information and communication technologies (ICT) in a pandemic on the basis of comparison of Belarus and Russia. Two research cases of adaptation are compared. Russian research materials covered two stages of functioning the higher education system: during the full transition to distance learning (DL) in Spring 2020, and in the end of 2020 when the institutions of higher education (HEIs) used DL selectively. In Belarus, DL was used partially. Belarusian case is presented by the data of the representative republican online survey conducted in Spring 2021. Survey materials at the Belarusian State University (December 2020 and February 2021) were also used to compare the opinions of students and employees. The Russian and Belarusian research data were compared by issues related to adaptation to DL and its future perspective. It was found that the level of adaptation of the Russian higher education system steadily increased, although differentiations between the HEIs remained. In Belarus, students' assessment of the quality of DL was generally positive, and adaptation strategies were successful. The results demonstrate an increase in the level of adaptation to the challenges of the pandemic. They revealed the educational potential of DL and confirmed the possibility of successful digitalization of higher education systems. This approach will help maintain competitiveness, the quality of higher education, increase the level of digital literacy and competence of students and teachers.